HUBUNGAN SUHU DAN KELEMBAPAN DENGAN TINGKAT DEHIDRASI PADA PEKERJA PENGASAPAN IKAN - Nensi Kristin Ningsih (The Indonesian Journal of Public Health, 2019)
Dehydration is a condition when body loses or lacks liquid or water. Dehydration can occur due to an internal factor such as person’s characteristics, and external factors such as the physical condition of environment, and environmental sanitation. An example of a person having the risk of dehydration is smoked fish workers because they are exposed to heat form burning dry coconut shells. The purpose of this study was to discover the correlation between worker characteristics, the physical condition of environment as well as environmental sanitation, and dehydration level. This study used cross sectional design with 19 respondents, and samples were taken using simple random sampling technique. The study took place at RW 02 Kelurahan Kenjeran, Kecamatan Bulak, Surabaya starting from February 2018 until finished. Data were analyzed using cross tabulation, and statistic tests which were chi square and Kolmogorov smirnov with 95% confidence level. Data were collected by measurement, interview, observation, and examination. The results showed that there was correlation between the physical condition of environment which included temperature (p=0,003<0,05) and humidity (p=0,001<0,05). The conclusion of this study was that the physical condition of environment including temperature and humidity had an important role to the dehydration level of the smoked fish workers.